2012
DOI: 10.1088/1367-2630/14/8/083012
|View full text |Cite
|
Sign up to set email alerts
|

Observation of energetic terahertz pulses from relativistic solid density plasmas

Abstract: We report the first experimental observation of terahertz (THz) radiation from the rear surface of a solid target while interacting with an intense laser pulse. Experimental and two-dimensional particle-in-cell simulations show that the observed THz radiation is mostly emitted at large angles to the target normal. Numerical results point out that a large part of the emission originates from a micron-scale plasma sheath at the rear surface of the target, which is also responsible for the ion acceleration. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 29 publications
(33 reference statements)
5
34
0
Order By: Relevance
“…Similar spatial distribution of THz radiation is recently measured 6 from the target back [14], and it is reported that a tiny hollow zone locates at the center and the peak at the far end from the center. This kind of angular distribution is unsurprisingly similar to that of TR from a weakly relativistic electron [18].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Similar spatial distribution of THz radiation is recently measured 6 from the target back [14], and it is reported that a tiny hollow zone locates at the center and the peak at the far end from the center. This kind of angular distribution is unsurprisingly similar to that of TR from a weakly relativistic electron [18].…”
supporting
confidence: 83%
“…It has been reported that the ultrashort electron bunches accelerated in the laser wakefield in underdense plasma can emit strong THz emission at the plasmavacuum boundary via the CTR mechanism [12]. It was also observed in experiments that the interaction of ultrashort intense laser pulses with solid targets can produce strong THz radiation [13,14].…”
mentioning
confidence: 99%
“…Laser-driven ion accelerators extend the unique possibility to generate multiple high-power tunable terahertz pulses with variable time delay, which will enable pump-probe studies in materials, otherwise not feasible (Jones et al, 1993;Back et al, 1998;Kampfrath et al, 2013). In our earlier work, we showed that high-power broadband terahertz pulses are emitted by the transient sheath field which is also responsible for the acceleration of protons and ions during laser-solid interaction (Gopal et al, 2012(Gopal et al, , 2013a.…”
Section: Introductionmentioning
confidence: 95%
“…Measurement of the radiation emitted from such plasmas provides a powerful diagnostic tool to explore their evolution. For example, THz radiation emission can be used to diagnose the movement of fast electrons along the target front surface [1][2][3] and to diagnose the evolution of plasma at the target rear surface [4] . In addition, the development of relatively compact high-power laser-driven THz sources could find applications, for example, in inducing phase transitions in material science [5][6][7] and for imaging in biology and medicine [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Email: ytli@iphy.ac.cn Previous studies have shown that THz emission is particularly strong when foil targets are used at the focus of a high-power laser pulse. Strong THz emission is induced at both the front [3] and rear surfaces [4] . The sensitivity of THz generation to laser pulse and interaction parameters (such as the pulse energy, polarization, and incident angle) were reported in both 100-femtosecond-level (or even shorter) duration regimes and in the weakly relativistic or nonrelativistic intensity regimes [3,[10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%